2001
DOI: 10.1097/00007890-200108150-00015
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Accelerated Loss of Kidney Function in Living Kidney Donors: Results From a Cross-Sectional Follow-Up1

Abstract: On average, the remaining renal function of kidney donors did not deteriorate more rapidly than what may be expected from ageing. However one-third of the female and half of the male donors developed hypertension and, approximately, 10% displayed proteinuria. Nevertheless, our study supports the continued use of living kidney donors if strict criteria are used for acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
2
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(152 citation statements)
references
References 25 publications
7
131
2
11
Order By: Relevance
“…Outcome data from transplantation studies (20)(21)(22) have long supported that CKD after total nephrectomy is not a major concern in patients with two equivalent functioning kidneys and normal preoperative concentration of serum creatinine, since donors submitted to nephrectomy do not show decrease of their kidney function, kidney failure needing dialysis, or death. However, this is not observed in patients submitted to RN for cortical renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome data from transplantation studies (20)(21)(22) have long supported that CKD after total nephrectomy is not a major concern in patients with two equivalent functioning kidneys and normal preoperative concentration of serum creatinine, since donors submitted to nephrectomy do not show decrease of their kidney function, kidney failure needing dialysis, or death. However, this is not observed in patients submitted to RN for cortical renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish study, the average estimated GFR (12 years after donation) was 72±18% of the age-predicted value. The ratio of the estimated to the predicted GFR showed no correlation to the time since donation, indicating that there is no accelerated loss of renal function after donation (Fehrman-Ekholm I, et al 2001 ). These results demonstrated that although living kidney donor lose GFR by 15-25%, they usually do not show the accelerated loss of renal function if they do not have risk factor for chronic renal disease (CKD).…”
Section: Renal Function Following Living Kidney Donationmentioning
confidence: 98%
“…Another study showed, in a live kidney donor cohort with a 93% retrieval rate of the 152 donors, fifty six percent of donors developed proteinuria (>150 mg/day), but only 10% had albuminuria (Gossmann J, et al 2005). By analysis of 402 outcome after donor nephrectomy in Sweden, significant proteinuria (> or =1.0 g/L) was found in 3% and slight proteinuria (<1.0 g/L) in 9% of the donors and proteinuria was associated with hypertension and a lower GFR (Fehrman-Ekholm I, et al 2001). One Meta-analysis, which analyzed a total of 5048 donors from forty-eight studies with an average follow-up of 7 years after donation (range 1-25 years), demonstrated that the average 24-h urine protein was 154 mg/day and concluded that kidney donation results in small increases in urinary protein.…”
Section: Proteinuria Following Living Kidney Donationmentioning
confidence: 99%
See 1 more Smart Citation
“…Az MDK-és IDK-betegcsoportok közötti különbség ellenére a folyamatosan bővülő transzplantációs várólis-ták szükségessé teszik a donorkritériumok kiterjesztését, és így a transzplantáció lehetőségét [12][13][14][15][16]. A dialízis-kezelésben részesülő betegek életminősége és hosszú távú túlélése rosszabb, mint a marginális donorokból származó vesével transzplantált betegeké.…”
Section: Megbeszélésunclassified